A descriptive single‐centre experience of the management and outcome of maternal alloantibodies in pregnancy. Issue 4 (13th June 2017) - Chatziantoniou, V.; Heeney, N.; Maggs, T.; Rozette, C.; Fountain, C.; Watts, T.; Harrison, C.; Pasupathy, D.; Sankaran, S.; Kyle, P.; Robinson, S.
SUMMARY: Background: Haemolytic disease of the fetus and newborn (HDFN) occurs when maternal IgG alloantibodies to fetal red blood cell antigens cross the placenta, causing haemolysis in the fetus and/or neonate. After delivery, the main concern is hyperbilirubinaemia, which can cause neurological damage. Objectives: To summarise our current management and outcome data to inform health‐care professionals counselling women whose pregnancies are at risk of HDFN and to compare these data with relevant studies. Methods: This is a retrospective descriptive study of all high‐risk pregnancies at risk of HDFN at Guy's and St. Thomas' NHS Foundation Trust (GSTFT) Maternity Unit over a 7‐year period. We defined high‐risk pregnancies as those in whom anti‐D, anti‐c, anti‐K or high (>32 or doubling strength) titres of all other antibodies were identified. Results: A total of 130 pregnancies in 112 women were followed up. A single alloantibody was found in 93 pregnancies (71.5%) and multiple alloantibodies in 37 pregnancies (28.5%). Anti‐D was most commonly encountered ( n = 48, 36.9%), followed by anti‐c ( n = 31, 23.8%) and anti‐E ( n = 15, 11.5%). In 65 of 130 pregnancies (50%), antibody concentrations triggered scans to screen for fetal anaemia. Of 130 pregnancies, 6 (4.6%) required intrauterine transfusions, and 31 of 130 (26%) neonates required post‐natal intervention. Overall, morbidity was 0.1% and mortality 0.002%. Conclusions: This study demonstrates that morbidity and mortality caused by HDFN is minimal. These results are reassuring for women at risk of HDFN as even severely affected cases are successfully managed in most instances. Further studies are needed to identify predictors of disease severity.